Perbandingan Reksa Dana Pendapatan Tetap Syariah dan Reksa Dana Saham Syariah Berdasarkan Tingkat Pengembaliannya Pada Periode Januari 2011 - Desember 2014 - Samsidar Widiarso; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
This research aims to know the comparison of the rate of return on fixed income mutual funds stock mutual funds and the Islamic Shariah from January 2011 to December 2014. The research method used is the quantitative approach. Variable used is the return value of the net assets of mutual funds, fixed income and net asset value of mutual fund shares. As for the analytical techniques used are paramatrik statistical hypothesis test using two sample is not paired and test the average difference T-Test.Based on the results of the research there is, normality test variables that are not distributed normally so do test Mann-Whitney on a variable with a result of 757.000 with significance value of 0.039. Then there is asignificant difference in the rate of return fixed income mutual funds stock mutual funds and the Islamic Sharia.